MEMENUHI KEADILAN BAGI MASYARAKAT DALAM KONTEKS PELAYANAN PENDIDIKAN (Studi Kasus Pungutan untuk Pendanaan Sekolah) - Agus Triono (Fakultas Hukum Universitas Lampung, 2021)
This article aims to explain how justice should be fulfilled in the context of educational services. In particular, the authors analyzed the charges for school funding that are currently rife—based on the analysis, that the collection of levies from the community for school funding is permitted according to statutory regulations with various restrictions. As a government legal action, the collection of these levies can have legal consequences. It can be declared invalid, invalid and not legally binding because they have violated applicable laws, thus causing an injustice to the community. Therefore, the collection of levies must be carried out legally, transparently and accountably. Thus the community can obtain legal certainty and justice and can actively participate in the development process and improve the quality of education. Withdrawal of donations can generally be requested but must fulfil the essence of a sense of justice. As a legal action the government, in this case, is the education unit or school management, it must still be held accountable if it results in injustice. This injustice can be in the form of an act of abuse of authority, confusing authority or acting arbitrarily, which is included in the criteria of maladministration. The research method used in this article is normative and qualitative data management. The suggestion that can be conveyed is that the government must optimize the applicable laws and provide even stricter sanctions for justice for society.